Ordinances of the City of Nashville, § 738, in Digest of the Ordinances of the City of Nashville, to Which are Prefixed the State Laws Incorporating, and Relating to, the City, with an Appendix Containing Various Grants and Franchises, at 364-65 (1893) - (:unkn) unknown (My University, 1893)
Prohibited the carrying of a pistol, Bowie knife, dirk knife, slungshot, brass knucks, or other deadly weapon. Punishable by fine of $10-50 for a first offense and $50 for subsequent offenses.
Keywords: CARRY